The foreign policy and intervention behavior of Africa's middle powers an analytic eclecticism approach - Amao, Olumuyiwa Babatunde (Lexington Books, 2024)
"This book highlights how the foreign policy and intervention behavior of state actors are influenced by regional hegemonic interests and collective identity, drawing from empirical insights gathered from structural realism and social constructivism to explain why and how states intervene in conflicts"--
Keywords: Geschichte; Intervention -- Völkerrecht; Außenpolitik; Bürgerkrieg in Sierra Leone -- 1991-2002; Bürgerkrieg in der Demokratischen Republik Kongo -- 1997-; Südafrika; Nigeria; Humanitarian intervention / Africa, Sub-Saharan; Nigeria / Foreign relations / Africa, Sub-Saharan; South Africa / Foreign relations / Africa, Sub-Saharan; Droit d'ingérence humanitaire / Afrique subsaharienne; Nigeria / Relations extérieures / Afrique subsaharienne; Afrique du Sud / Relations extérieures / Afrique subsaharienne; Diplomatic relations; Humanitarian intervention; South Africa; Sub-Saharan Africa